Family Planning Services in Covid-19 Pandemic: A Scoping Review - Sari, Riska Dwi Pramita; Hakimi, Mohammad; Mufdlilah, Mufdlilah; Anjarwati, Anjarwati (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The spread of the Covid-19 virus, which has been stated as a global pandemic by WHO in March 2020, has given impacts on all sectors, one of the impacts on maternal health is the change and disturbance in family planning (FP) services. This review to identify the theme mapping of the literature regarding FP services during the Covid-19 pandemic. The drafting of the ScR adopted Preferred Reporting Items for Systematic Reviews and Meta-Analyzes Protocols for Scoping Reviews (PRISMA-ScR). There were 3 mapping themes obtained, namely the impact of the Covid-19 pandemic towards FP services, the influencing factors of FP services, and the recommendations for FP services during the Covid-19 pandemic. A lot of research is needed, especially those related to the practice of effective FP services and the quality of FP services to develop strategies for the improvement of FP services in the upcoming new normal era.